Estimation of serum bilirubin level as a diagnostic laboratory marker of acute appendicitis and its role in prediction of appendicular perforation - Ghosh, Manoranjan; Monali Patole Mukherjee,; Chaturvedi, Vikram; Dipankar Mukherjee, (Asian Journal of Medical Sciences, 2023)
Background: Acute appendicitis is the most common cause of surgical abdomen. A delay in diagnosis and subsequent delay in intervention may lead to appendicular perforation which leads to peritonitis and further complications including death. In this study, we tried to evaluate – “Estimation of serum bilirubin level as a diagnostic laboratory marker of acute appendicitis and its role in prediction of appendicular perforation.” Aims and Objectives: The objectives of the study are as follows: To study the relationship between hyperbilirubinemia and acute appendicitis and to evaluate its credibility as a diagnostic marker for acute appendicitis. To evaluate whether elevated Bilirubin levels have a predictive potential for diagnosis of appendicular perforation. Materials and Methods: Patients clinically diagnosed with acute appendicitis, supported by imaging studies, who gave consent for the study were included in the study. All those patients underwent estimation of serum bilirubin levels along with other investigations. Data collected were compiled and analyzed. Results: In this study, among 408 patients, sensitivity of serum bilirubin in predicting acute appendicitis was 74.59%. Specificity of serum bilirubin in predicting acute appendicitis was 12.38%. Positive predictive value of serum bilirubin in predicting acute appendicitis was 71.06%. Negative predictive value of serum bilirubin in predicting acute appendicitis was 14.44%. Odds ratio was 0.4147. Conclusion: Serum Bilirubin level appears to be a promising marker for diagnosing acute appendicitis and perforation.